Nonlinear dynamic mechanism of rolling element bearings with an internal clearance in a rotor-bearing system. (November 2016) - Nan, Guofang; Tang, Min; Chen, Eryun; Yang, Ailing
Rolling element bearing is a key component in the rotating machinery, especially in the rotor-bearing system which often shows a complex nonlinear dynamic characteristic due to the presence of the internal clearance between the rolling elements and the races. A nonlinear model of the rotor-bearing is developed and the nonlinear dynamic analysis is carried out in this article. The dynamic equations are derived based on the Hertzian contact theory, considering whether there existed an internal clearance between a rolling element and the races at a moment and how much the contact force of the rolling element is during the interface. With the help of the bifurcation diagrams, Poincare maps and the orbit of center for the axis, the effect of the rotating speed, the clearance, and the stiffness on the dynamic response are investigated. The bearing system exhibits the complicated dynamic behaviors such as the periodic motion, the quasi-periodic motion, the chaos, and the jump phenomenon; the rolling element system is sensitive to the variation of the rotating speed, the clearance, and the stiffness in some ranges. The results are meaningful to the practical prediction of the vibrational response; the work is significant in theoretical understanding of the nonlinear dynamic mechanism. This research offers an analytical method to check the parameters to prevent the bearings from the dangerous working conditions.